ASSORTMENT PRICING IN THE FIELD OF MARKETING INNOVATION - ORLOV, Oliver; RYASNYKH, Evgenia; SAVCHENKO, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The modern world is in a period of rapid structural change that affects all spheres of life, and to survive in this competitive environment, companies must respond to these changes in a timely manner. Against the background of new requirements, the crisis of existing planning methods and especially pricing for new products is clearly visible. The article provides a critical analysis of assortment pricing, proves the unsuitability of traditional methods of managing changes in the range of products of enterprises under conditions of multi-item production. A new approach to solving this topical problem with the use of margin analysis tools is proposed. The article emphasizes that the impact of reduction (or increase) in prices for specific products on profitability and profitability can not be considered in isolation from the range and range of products in general for the enterprise. The authors believe that the main role in making decisions to reduce or increase prices for specific products is played by the coefficient of marginal profit. It is proved that assortment pricing can be implemented only with the help of a marginal approach, in which the break-even point is played by the break-even factor and the reliability margin. The proposed method of calculation has the character of direct influence, has no analogues in foreign and domestic literature and practice, does not require additional resources and time. The proposals themselves are very simple and have an internal logic.